Lupinus albus protein componentes inhibit MMP-2 and MMP-9 gelatinolytic activity in vitro and in vivo - Mota, Joana (2021)
Matrix metalloproteinases 2 and 9 (MMP-2 and MMP-9) are regarded as important clinical targets due to their nodal-point role in inflammatory and oncological diseases. Here, we aimed at isolating and characterizing am MMP-2 and-9 inhibitor (MMPI) from Lupinus albus and at assessing its efficacy in vitro and in vivo. The protein was isolated using chromatographic and 2-D electrophoretic procedures and sequenced by using MALDI-TOF TOF and MS/MS analysis. In vitro MMP-2 and 9 inhibitions were determined on colon adenocarcinoma (HT29) cells, as well as by measuring the expression levels of genes related to these enzymes. Inhibitory activities were also confirmed in vivo using a model of experimental TNBS-induced colitis in mice, with oral administrations of 15 mg kg1. After chromatographic and electrophoretic isolation, the L. albus MMP-9 inhibitor was found to comprise a large fragment from -conglutin and, to a lower extent, small fragments of -conglutin. In vitro studies showed that the MMPI successfully inhibited MMP-9 activity in a dose-dependent manner in colon cancer cells, with an IC50 of 10 g mL1 without impairing gene expression nor cell growth. In vivo studies showed that the MMPI maintained its bioactivities when administered orally and significantly reduced colitis symptoms, along with a very significant inhibition of MMP-2 and -9 activities. Overall, results reveal a novel type of MMPI in lupine that is edible, proteinaceous in nature and soluble in water, and effective in vivo, suggesting a high potential application as a nutraceutical or a functional food in pathologies related to abnormally high MMP-9 activity in the digestive system